Penerapan Sistem Akuntansi Pada Usaha Mikro Kecil dan Menengah Kecamatan Pandenglang Kabupaten Pandeglang Provinsi Banten - Yoyoh guritno (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
Abstract MSMEs become one of the important drivers in building the country's economic strength because MSMEs can create jobs more quickly than other business sectors, have the ability to adapt to economic crisis conditions and contribute greatly to Bruto.. So far, MSMEs have contributed 57-60% of the Gross Domestic Product (PBD) and the employment rate is around 97% of the entire national workforce (MSME Business Profile by LPPI and BI in 2015). Good fund management is an important factor that can lead to the success or failure of MSMEs in addition to other factors. A good way to manage funds is to apply good accounting. This research aims to identify the application of accounting records and the presentation of financial statements and an understanding of the accounting standards of entities without public accountability (SAK ETAP). The results of this study indicate that the majority of MSME managers do not implement an accounting system and only 9% of MSMEs understand SAK ETAP and only 7% of MSMEs implement accounting systems and present financial reports in full according to SAK ETAP. This is due to the level of education of most of the SMPs and SMA and lack of interest in implementing an accounting system as well as a lack of socialization about the accounting system and SAK ETAP from the relevant local government